مدى تحقيق أداوات التمويل الخضراء للتنمية المستدامة Scope of green financing instruments to achieve sustainable development - Negasi, Mohamed Ibrahim; Laeba, Muhammad; Mohamed Zaki, Hesham Mahmoud (IIUM Journal Publication Unit, 2019)
This paper addresses the issue of achieving sustainable development through green financing instruments, where it discusses the meaning of green bonds and Sukuk, the steps of their issuance, their dimensions and characteristics. The paper also examines the provision of Shariah on green bonds and Sukuk and discusses the extent of their capability to achieve sustainable development of society. This study uses the inductive approach to track the opinions of researchers on the subject as well as the analytical approach to analyze those opinions . The study has reacheda number of conclusions, the most important of which are: the impermissibility of dealing with green bonds because they are based on riba. Likewise, green Sukuk is also not permissible in Shariah because of the suspicion of riba in it, as it is recovered at nominal value, and these financing instruments do not contribute to the achievement of sustainable development to the highest degree as expected. .